UJI PERKEMBANG BIAKAN MISELIA BIBIT JAMUR TIRAM PUTIH (Pleorutus ostreatus) DENGAN SUBSTRAT CAMPURAN AIR KELAPA DAN AIR LERI - Rahayu, Sri; Martono, Djoko Setyo (JURNAL AGRI-TEK, 2015)
Development of fungal productivity is largely determined by the quality seeds. The problems faced by the poor quality of the field seeds obtained from breeder seed farmers. The research objective produce quality seedlings with a substrate mixture of coconut water and water leri. Research conducted at the Laboratory of the Faculty of Agriculture Unmer Madison research methodology using Random Design Factorial one factor comprises 11 treatment was repeated three times with the sample number 5. Treatment consists of L 0 (without coconut milk), L 1 (Without water leri), L 2 (water oil concentration of 10 ml: 90 ml of water leri), L 3 (coconut water concentration of 20 ml: 80 ml of water leri), L 4 (coconut water concentration of 30 ml: 70 ml of water leri) L 5 (coconut water concentration of 40 ml: 60 ml of water leri), L 6 (coconut water concentration of 50 ml: 50 ml of water leri), L 7 (coconut waterconcentration of 60 ml: 40 ml of water leri), L 8 (coconut water concentration of 70 ml: 30 ml of water leri), L 9 (concentration of coconut water 80 ml: 20 ml water waste leri), L 10 (concentration of coconut water 90 ml: 10 ml of water leri). The observation parameter consists of mycelial growth rate, the amount of mycelia, mycelia long and wide spread of mycelia. The data collected was analyzed variance to test Duncant 5% and diagram proliferation . Statistical analysis showed a concentration of coconut water treatment applications 60 ml: 40 ml of water leri (L 7) gave the highest average value on the amount of mycelia parameters and wide spread of mycelia parameter, followed by treatment of the concentration of coconut water applications 50 ml:50 ml of water leri (L 6) gave the highest average value on the mycelial growth rate and mycelia long.Keywords: white oyster mushroom mycelia, substrates coconut water and water leri.